Subsurface and through-wall SAR imaging techniques for ground penetrating radar - Unal, M.; Caliskan, A.; Turk, A. S.; Bakbak, P. O. (Technology and design in electronic equipment, 2013)
This paper presents some useful signal processing and synthetic aperture radar imaging techniques for ultra-wide band (UWB) ground penetrating radar. Novel UWB antenna structures are experimentally designed in this work. Raw and processed data collected in the course of experimental studies of subsurface sensing and through-wall imaging scenarios are demonstrated in B-scan and C-scan target images.